Large Barkhausen jump in Fe/Co laminated films - Norimichi Watanabe; Atsushi Matsuo; Susumu Abe; Akiyoshi Nakayama (AIP Advances)
When torsional stress is applied to a Fe–Co–V wire and a magnetic field is applied in the longitudinal direction of the wire, a pulse voltage is generated in the search coil wound around the wire due to a large Barkhausen jump. This pulse voltage has the characteristic that a pulse waveform with a constant magnitude can be obtained regardless of the rate of change of the external magnetic field, and the wire can be applied to rotation detection sensors. In this study, we fabricated Fe/Co laminated films to generate a large Barkhausen jump in magnetic thin films. We observed a constant pulse voltage, even when the frequency of the external magnetic field was less than 10 Hz, and we observed a large Barkhausen jump in the magnetic thin film.